1991
DOI: 10.1093/oxfordjournals.humrep.a137271
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine release of oestriol in castrated rhesus monkeys induces local but not peripheral oestrogenic effects: a possible approach for the treatment and prevention of Asherman's syndrome

Abstract: Two types of oestrogen-medicated intrauterine devices (IUD) were studied in ovariectomized rhesus monkeys. An oestradiol (E2) fibre-wrapped IUD that released E2 at a rate of 3.57 micrograms/cm/day, or an oestriol (E3) fibre-wrapped IUD that releases E3 at a rate of 6.4 micrograms/cm/day, was inserted in eight animals and left in place for 4 weeks. Serum levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), E2 and E3 were determined by radioimmunoassay for 1 week before the IUD insertion, duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Investigation Asch et al (1991) inserted oestrogen fibre-wrapped IUD into the uteri of castrated rhesus monkeys. The devices induced marked endometrial proliferation and the authors suggested that such a device might provide the same efficacy as oral oestrogen treatment but without the systemic side effects.…”
Section: Timely Surveillance Of Subsequent Pregnanciesmentioning
confidence: 99%
“…Investigation Asch et al (1991) inserted oestrogen fibre-wrapped IUD into the uteri of castrated rhesus monkeys. The devices induced marked endometrial proliferation and the authors suggested that such a device might provide the same efficacy as oral oestrogen treatment but without the systemic side effects.…”
Section: Timely Surveillance Of Subsequent Pregnanciesmentioning
confidence: 99%
“…Asch et al placed estrogen fiber-wrapped IUDs into the uteri of castrated rhesus monkeys to induce marked endometrial proliferation and suggested that such a device might provide the same efficacy as oral estrogen treatment but without the systemic side effects. 55 Some studies using sildenafil (Viagra) 100 mg vaginally or 6 mg of L-arginine (which may strengthen blood vessels) daily have shown increased endometrial thickness and an improvement in radial artery-resistance indexes. 56 There are encouraging, but scanty data demonstrated thickened endometrium after a 6-month use of pentoxifylline (800 mg/day) and vitamin E (1000 IU/ day).…”
Section: Investigationmentioning
confidence: 99%
“…En 1991, Asch et al [12] rapportaient dans une étude l'utilisation de deux types de dispositifs intra-utérins (DIU) aux estrogènes (oestradiol et oestriol) laissés pendant trois semaines chez des singes rhésus ovariectomisés. Les auteurs analysaient alors les taux circulants d'oestradiol, de FSH, de LH et les effets sur la muqueuse utérine.…”
Section: Physiopathologie Des Synéchiesunclassified